Sex pheromone and trail pheromone of the sand termite Psammotermes hybostoma - Sillam-Dussès, David; Hanus, Robert; Abd El-Latif, Ashraf Oukasha; Jiroš, Pavel; Krasulová, Jana; Kalinová, Blanka; Valterová, Irena; Sobotník, Jan (Journal of chemical ecology, 2011)
Within the complex network of chemical signals used by termites, trail pheromones and sex pheromones are among the best known. Numerous recent papers map the chemical identity and glandular origin of these pheromones in nearly all major isopteran taxa. In this study, we aimed to describe the sex pheromone and the trail pheromone of a poorly known sand termite, Psammotermes hybostoma. We identified (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol (dodecatrienol) as the sex pheromone released by tergal and sternal glands of female imagos and, at the same time, as the trail pheromone secreted from the sternal gland of workers. We conclude that chemical communication in Psammotermes does not differ from that of most other Rhinotermitidae, such as Reticulitermes, despite the presence of a diterpene as a major component of the trail pheromone of Prorhinotermes to which Psammotermes is presumed to be phylogenetically close. Our findings underline once again the conservative nature of chemical communication in termites, with dodecatrienol being a frequent component of pheromonal signals in trail following and sex attraction and, at the same time, a tight evolutionary relationship between the trail following of working castes and the sex attraction of imagos.
Keywords: sexuální lákadla; Isoptera; Animals; Polyenes; polyeny; Female; mužské pohlaví; zvířata; sexuální chování zvířat; Male; Sexual Behavior, Animal; Sex Attractants; ženské pohlaví